Guideline‐directed medical therapy implementation during hospitalization for cardiogenic shock - Matthew G. Dimond; Carolyn M. Rosner; Seiyon Ben Lee; Unique Shakoor; Taraneh Samadani; Wayne B. Batchelor; Abdulla A. Damluji; Shashank S. Desai; Kelly C. Epps; M. Casey Flanagan; Hala Moukhachen; Anika Raja; et al. (ESC Heart Failure)
Abstract Aims Despite significant morbidity and mortality, recent advances in cardiogenic shock (CS) management have been associated with increased survival. However, little is known regarding the management of patients who survive CS with heart failure (HF) with reduced left ventricular ejection fraction (LVEF, HFrEF), and the utilization of guideline‐directed medical therapy (GDMT) in these patients has not been well described. To fill this gap, we investigated the use of GDMT during an admission for CS and short‐term outcomes using the Inova single‐centre shock registry. Methods We investigated the implementation of GDMT for patients who survived an admission for CS with HFrEF using data from our single‐centre shock registry from January 2017 to December 2019. Baseline characteristics, discharge clinical status, data on GDMT utilization and 30 day, 6 month and 12 month patient outcomes were collected by retrospective chart review. Results Among 520 patients hospitalized for CS during the study period, 185 (35.6%) had HFrEF upon survival to discharge. The median age was 64 years [interquartile range (IQR) 56, 70], 72% (n = 133) were male, 22% (n = 40) were Black and 7% (n = 12) were Hispanic. Forty‐one per cent of patients (n = 76) presented with shock related to acute myocardial infarction (AMI), while 59% (n = 109) had HF‐related CS (HF‐CS). The median length of hospital stay was 12 days (IQR 7, 18). At discharge, the proportions of patients on beta‐blockers, angiotensin‐converting enzyme inhibitors (ACEis)/angiotensin receptor blockers (ARBs)/angiotensin receptor/neprilysin inhibitors (ARNIs) and mineralocorticoid receptor antagonists (MRAs) were 78% (n = 144), 58% (n = 107) and 55% (n = 101), respectively. Utilization of three‐drug GDMT was 33.0% (n = 61). Ten per cent of CS survivors with HFrEF (n = 19) were not prescribed any component of GDMT at discharge. Multivariable logistic regression adjusted for baseline GDMT use revealed that patients with lower LVEF and those who transferred to our centre from an outside hospital were more likely to experience GDMT addition (P < 0.05). Patients prescribed at least one additional class of GDMT during admission had higher odds of 6 month and 1 year survival (P < 0.01): On average, 6 month survival odds were 7.1 times greater [confidence interval (CI) 1.9, 28.5] and 1 year survival odds were 6.0 times greater than those who did not have at least one GDMT added (CI 1.9, 20.5). Conclusions Most patients who survived CS admission with HFrEF in this single‐centre CS registry were not prescribed all classes or goal doses of GDMT at hospital discharge. These findings highlight an urgent need to augment multidisciplinary efforts to enhance the post‐discharge medical management and outcomes of patients who survive CS with HFrEF.